Step 1: Setting variables.
Let
\[
y = \sin^{-1} \left(\frac{2x}{1 + x^2} \right), \quad z = \cos^{-1} \left(\frac{1 - x^2}{1 + x^2} \right)
\]
Step 2: Recognizing trigonometric identities.
We use the well-known identity:
\[
\sin(2\theta) = \frac{2 \tan \theta}{1 + \tan^2 \theta}
\]
which implies
\[
\sin^{-1} \left(\frac{2x}{1 + x^2} \right) = 2 \tan^{-1} x
\]
Similarly, we use
\[
\cos(2\theta) = \frac{1 - \tan^2 \theta}{1 + \tan^2 \theta}
\]
which gives
\[
\cos^{-1} \left(\frac{1 - x^2}{1 + x^2} \right) = 2 \tan^{-1} x
\]
Step 3: Differentiating both functions.
\[
\frac{dy}{dx} = \frac{d}{dx} (2 \tan^{-1} x) = \frac{2}{1 + x^2}
\]
\[
\frac{dz}{dx} = \frac{d}{dx} (2 \tan^{-1} x) = \frac{2}{1 + x^2}
\]
Step 4: Computing \( \frac{dy}{dz} \).
\[
\frac{dy}{dz} = \frac{\frac{2}{1 + x^2}}{\frac{2}{1 + x^2}} = 1
\]
Thus, the correct answer is (A) \( 1 \).